Implementation of Business Process Re-engineering Concept For Improving Profit - Malika, Ika; Wahyani, Widhy (Inscientech: Journal of Industrial, Science and Technology, 2017)
National sugar production in the new millennium only reached 2.3 million tons per year, while the national sugar consumption reached 4.5 million tons per year. For that reason, so the government should encourage sugar mills to diversify the products immediately. In producing sugar also generates solid waste such as blothong (: Javanesse). This study discusses the implementation of the concept of Business Process Re-engineering (BPR). BPR concept is used to design the sugar mill Business management in order to optimize itâs resources, so it is marketable. Under researcher observation, Lestari sugar mill, do not optimize in using of waste as a second output of sugar production yet. Solid waste utilization as briquette also helps the government in developing new renewable energy that can be optimized. As known Lestari sugar mill has not been used solid waste optimally and this research recommend for designing new business management, which reprocess blothong waste to be used as briquettes in order to increase profit. An outcome from the business management can increase profit as much as Rp 135.615.420.000,00 with the amount of total production cost as much as Rp 95.130.356.000,00 and having profit / gross loss from the Business as much as Rp 40.485.064.000,00. The proposal of the design of the business management gained more profit as pointed Rp 156.797. 670.000,00 which is included briquettes Solid waste revenue. So, the total amount of new business management cost is Rp 95.718.455.000,00 and gaining profit/gross loss as much as Rp 61.079.115.000,00. That achievement was increase as much as 22% from the previous business management. Keywords: Business Process Re-engineering, sugar mill, renewable energy, innovation, production, briquettes, solid waste (blothong), profit.